Electrochemiluminescence of N,N'-Dimethylformamide Passivated Black Phosphorus Quantum Dots - He, Shuijian (Langmuir : the ACS journal of surfaces and colloids, 2024)
Black phosphorus quantum dots (BPQDs) have shown promising applications in biosensors and energy storage devices. However, the electrochemiluminescence (ECL) properties of pristine BPQDs in an organic system have rarely been reported. In this paper, N,N'-dimethylformamide passivated BPQDs with a small size of 2.3 nm were obtained by an ultrasonication-assisted liquid exfoliation process, and their ECL properties of BPQDs were studied. A reversible reduction peak was recorded by differential pulse voltammetry, while no apparent oxidation peak was observed. ECL signal was not seen in the annihilation route. Persulfate was proved to be an effective coreactant and yellow emission was observed which was greatly red-shifted in comparison to that of photoluminescence. ECL of BPQDs is believed to be generated from both the surface states and electron promotion over their band gap